Writing East : the "travels" of Sir John Mandeville - Higgins, Iain Macleod (Middle Ages series., 1997)
"A remarkable analysis of an important medieval text. ... This work will surely initiate new studies of the precolonial frame of mind and the role of distinct versions of medieval manuscripts in the shaping of medieval understanding."--Sixteenth Century Journal.